Effect of Change in USMLE Step 1 Grading on Orthopaedic Surgery Applicants: A Survey of Orthopaedic Surgery Residency Program Directors. (May 2021) - Gu, Alex; Farrar, Jacob; Fassihi, Safa C.; Stake, Seth; Ramamurti, Pradip; Wei, Chapman; Wessel, Lauren E.; Fufa, Duretti T.; Rao, Raj D.
Abstract : Introduction: Recently, the Federation of State Medical Boards and the National Board of Medical Examiners, cosponsors of the United States Medical Licensing Examination (USMLE), changed the USMLE Step 1 results from a three-digit score to a pass/fail format. The purpose of this study was to analyze the opinions of program directors (PDs) to predict how the evaluation of orthopaedic surgery residency applicants will change following the change. Methods: A 17-question online survey was distributed to PDs via e-mail. This survey covered program demographics, questions regarding the relative importance of various factors for selection of interviews, and perceived changes and effect of the scoring change. Responses were aggregated and analyzed. Results: PDs indicated that the three highest scored factors were (1) failure in prior attempts in USMLE/COMLEX examinations (4.7), (2) audition elective/rotation within your department (4.5), and (3) personal prior knowledge of the applicant (4.1). In addition, 38 PDs (81.1%) anticipate that they will require USMLE Step 2 clinical knowledge scores for interview consideration. Conclusion: Most orthopaedic surgery PDs think that the change in score reporting for the USMLE Step 1 will result in additional requirements and changes in how programs select applicants and do not support the decision.